2016
DOI: 10.1159/000455026
|View full text |Cite
|
Sign up to set email alerts
|

Complex X-Chromosomal Rearrangements in Two Women with Ovarian Dysfunction: Implications of Chromothripsis/Chromoanasynthesis-Dependent and -Independent Origins of Complex Genomic Alterations

Abstract: Our current understanding of the phenotypic consequences and the molecular basis of germline complex chromosomal rearrangements remains fragmentary. Here, we report the clinical and molecular characteristics of 2 women with germline complex X-chromosomal rearrangements. Patient 1 presented with nonsyndromic ovarian dysfunction and hyperthyroidism; patient 2 exhibited various Turner syndrome- associated symptoms including ovarian dysfunction, short stature, and autoimmune hypothyroidism. The genomic abnormaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…It has been suggested that 70% of complex rearrangements are associated with a normal phenotype [Pellestor et al, 2011]. Consistent with this, we identified X chromosomal chromothripsis in a woman who showed no apparent clinical features except for ovarian dysfunction and hyperthyroidism [Suzuki et al, 2016]. The relatively mild phenotype of this woman can be explained by the selective inactivation of the rearranged X chromosome.…”
Section: Chromothripsissupporting
confidence: 86%
“…It has been suggested that 70% of complex rearrangements are associated with a normal phenotype [Pellestor et al, 2011]. Consistent with this, we identified X chromosomal chromothripsis in a woman who showed no apparent clinical features except for ovarian dysfunction and hyperthyroidism [Suzuki et al, 2016]. The relatively mild phenotype of this woman can be explained by the selective inactivation of the rearranged X chromosome.…”
Section: Chromothripsissupporting
confidence: 86%
“…Some chromoanagenesis events arise de novo, but accumulating data on familial chromoanagenesis-mediated rearrangements have validated the notion of the heritability of chromoanagenesis-mediated genomic alterations [12,34]. Recent reports have provided evidence that chromoanagenesis can operate in human germline cells and during early embryonic development [35][36][37], strongly suggesting that chromoanagenesis could be more common than anticipated in gametes and preimplantation embryos.…”
Section: All-in-onementioning
confidence: 99%
“…Our recent study exemplified the 'recurrent DNA damage' model (7). In this study, we identified an X chromosomal rearrangement in a girl clinically diagnosed with Turner syndrome.…”
Section: Classical View Of Complex Genomic Rearrangementsmentioning
confidence: 90%
“…The phenotypes of germline X chromosomal rearrangements are ascribable to chromosomal imbalances and dysregulation of X chromosomal genes that escape inactivation. Additionally, complex X chromosomal rearrangements may perturb the DNA methylation status in some genes that usually escape X inactivation (7). It is worth mentioning that germline complex rearrangements are not necessarily pathogenic.…”
Section: Clinical Consequences Of Complex Genomic Rearrangements In Tmentioning
confidence: 99%
See 1 more Smart Citation